Subcicatricial fat grafting associated with rigotomy: a clinical and microstructural analysis - Auro Marcos Levy de Andrade Filho; Bruno Peres Vidal; Ana Paula Girol; Helena Ribeiro de Souza; Mairton Geromel; Manoel Alves Vidal (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: The increase in survival of large burn patients during the acute phase has also increased the prevalence of esthetic-functional scarring sequelae. With regard to the clinical relevance of subcicatricial fat grafting, the actual changes after the procedure need to be understood and microscopically evaluated. METHODS: Eight patients with alcohol burns, with an average time after burn of 12 months (10-14 months), who underwent subcicatricial fat grafting associated with rigotomy were selected. Skin biopsies were performed in before and 14 weeks after operation. The following issues were assessed: 1) esthetic-functional improvement of the scar, by using the Vancouver scar scale; 2) quantitative and qualitative analyses of cicatricial collagen; 3) immunohistochemical analysis of scar vascularization with anti-vascular endothelial growth factor (anti-VEGF) antibody. RESULTS: When comparing the pre- and post-fat grafting period, a significant esthetic-functional improvement and, microscopically, a redefinition of the boundaries of the papillary and reticular dermis were observed, as well as quantitative reduction and reorganization of collagen, in addition to the decrease of the vascularization of the tissue through immunohistochemical analysis. CONCLUSION: The basic principle of the whole physiological healing process is to reestablish local homeostasis, that is, excessively intensified steps that lead to severe clinical changes. When subcicatricial fat grafting associated with rigotomy was performed, qualitative and quantitative improvements of the tissue were verified in this study. Thus, it becomes evident that this procedure can complement the treatment of cicatricial pathologies.